The Community Service of MI Teachers in Bumiayu District Using EKI (English for Kids) Application to Increase Students' Interest in Learning English - Nurdiawati, Dede; Achmad Syauqi; Akhmad Nurkholis; Asyifa Salsabilla; Dewinta Yuniar Firdaus (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
The purpose of this service is to foster students' interest in learning English. The service team partnered with KKGMI Bumiayu sub-district by involving 60 MI teachers as trainee and mentoring them. The provided technology and innovation to partners are android application of English for Kids (EKI), teacher module books, and student worksheets as supporting media for English learning in the classroom. We are carrying out the stages of situation analysis, licensing and coordination as well as the needs analysis, in doing this service activity we carry out 6 times of training and mentoring with MI teachers and students in Bumiayu sub-district. The results show that from 60 training participants, 80% of them increased their abilities by 70% in understanding English vocabulary and using the aplication. This service activity is also fully supported by the Chairperson of KKGMI, KKMI, MI supervisors as well as several school principals and it expected that the abilities of teachers will increase and able to use digital learning media in adapting to the recent.